Table of Contents - Introduction - M. Todd Brashears (Journal of International Agricultural and Extension Education, 2022)
The Journal of International Agricultural and Extension Education (JIAEE) is the official refereed publication of the Association for International Agricultural and Extension Education (AIAEE). The purpose of the JIAEE is to enhance the research and knowledge base of agricultural and extension education from an international perspective.